ANALISIS PENGARUH MOTIVASI KONSUMEN, PERSEPSI KUALITAS DAN SIKAP KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA DI KABUPATEN BANJARNEGARA - Agung Gangsar Rismanto, 05. 2502.0123; Suharmanto, Toto (Students Journal of Economic and Management, 2013)
The purpose of this research is so find out and analysis the effect of motivation, perception and consumerâs attitude through purchacing decision. The object of this reserct is âHONDA â a motorcycleâs brandâs user and buyers around Banjarnegara. Based on the result of this reserct know that motivation, perception and customerâs attituted influence Honda purchasing with positively and significantly through purchasing decision Honda a motorcycle brand. The benefit of this reserct is used a source of information for increasing sales volume amount through customerâs behavior.Key words: motivation, perception, consumerâs attitude and purchasing decision